Social trust, green finance, and enterprise innovation - Zan, Haocheng; Jiang, Kailin; Ma, Jing (Finance research letters, 2024)
•This study investigates the relationship between social trust and its impact on enterprise innovation.•This study analyzes the mediating role of green finance development on social trust and corporate innovation.•The study using 2010–2022 listed company data as the research sample. After COVID-19, economic development has been relatively unstable, and social trust has new requirements for corporate innovation. This article explores the impact of these factors using data for A-share listed companies in Shanghai and Shenzhen from 2010 to 2022 as research samples. The research results are as follows: (1) Social trust positively impacts promoting improved corporate innovation. (2) The development of green finance plays a partial intermediate role in social trust driving enterprise innovation. (3) Social trust has a more significant promoting effect on enterprise innovation at state-owned listed companies than it does at non-state-owned companies.